THE IMPORTANCE OF EDUCATION AND AWARENESS IN THE DIGITAL USE OF FAMILIES - Malatyinszki, Szilárd (Studia Mundi – Economica, 2022)
The livese of families have changed in recent decades – this change has accelerated in recent years. The rise of digital devices has changed time management (both work and leisure), working methods, and educational technology tools. With the onset of the virus situation, families were forced into their homes, so family members had to share assets, both in space and time. Working, educating, entertaining and managing life processes in an online space can only be done in a balanced way with sufficient awareness. In this awareness, family members can count on each other. In addition, a significant level of learning and socialization is required on the part of both adults and children. In order to work effectively, the employer must have management, control and motivation systems that also support a balanced family life.